PENGARUH MODEL REALISTIC MATHEMATICS EDUCATION (RME) BERBANTUAN GAME SCRATCH TERHADAP NUMERASI SISWA KELAS V - Alfina Damayanti; Via Yustitia; Danang Prayogo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Numeracy skills are essential competencies that enable elementary school students to solve mathematical problems in real-life contexts. However, students’ numeracy achievement remains relatively low due to the predominance of conventional teaching approaches. This study aimed to determine the effect of the Realistic Mathematics Education (RME) model assisted by Scratch game media on the numeracy skills of fifth-grade elementary school students. The study employed a quantitative approach using a quasi-experimental design with a posttest-only control group. The participants consisted of 32 fifth-grade students at SDN Sidokepung II Sidoarjo, divided into an experimental class (n = 16) and a control class (n = 16). Data were collected through an essay-based numeracy test and classroom observation sheets. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Mann–Whitney U test. The findings revealed that the experimental class achieved a higher mean posttest score (86.81) than the control class (47.62). The Mann–Whitney U test indicated a significance value of p < 0.001, demonstrating a statistically significant difference between the two groups. Furthermore, classroom implementation and student activity reached 92.5% and 89%, respectively, indicating very good learning quality. These findings suggest that the Realistic Mathematics Education model assisted by Scratch game media effectively improves elementary school students’ numeracy skills and promotes active participation during mathematics learning.